Targeted Lung Premetastasis Niche: Mechanisms, Strategies, and Application - Chenghao Cao; Di Lu; Huigang Li; Shen Pan; Jianyong Zhuo; Zuyuan Lin; Chiyu He; Peiru Zhang; Songmin Ying; Xuyong Wei; Shusen Zheng; Zhe Yang; et al. (MedComm)
ABSTRACT Lung metastasis remains a leading cause of cancer mortality, driven not only by primary tumors but crucially by dynamic interactions within the premetastatic niche (PMN). Emerging evidence reveals that organ‐specific PMN formation precedes tumor cell arrival, creating an immunosuppressive microenvironment conducive to metastatic colonization. Primary tumor‐derived factors interact with lung resident cells, promoting the recruitment of bone marrow‐derived cells and creating a favorable microenvironment for the migrating tumor cells. Despite progress, systematic integration of PMN's multilayered regulatory mechanisms—from mechanism to clinical application remains lacking. The review summarizes recent studies investigating the effects of PMN in the entire process of lung metastasis. Our discussion revolves primarily around extracellular vesicles, extracellular matrix remodeling, proinflammation, immunosuppression, angiogenesis, and metabolic reprogramming. We emphasize the impact of various treatment strategies for primary tumors on the PMN in clinical practice, while also summarizing current diagnostic methods and exploring new therapeutic possibilities in the PMN. Finally, we propose a roadmap for future investigations into the lung PMN, highlighting prioritized research axes that bridge mechanistic discoveries with bench‐to‐bedside translation of PMN‐targeted interventions.